Avaliação das alterações hematológicas, bioquímicas e genotóxicas nos trabalhadores expostos à agrotóxicos em municípios do estado do Piauí - Rodrigues, Vera Regina Cavalcante Barros (2011)
The use of pesticides in agriculture rapidly increased their consumption, especially indiscriminate consumption, being Brazil currently the largest market for pesticide in the world, representing 16% of worldwide sales. In the state of Piauí, the agricultural expansion in the region of Cerrado contributed to their increased use, exposing farm workers to damages to the DNA. The purpose of this study was to evaluate the toxic and genotoxic effects in farm workers exposed to pesticides in Piauí, with the use of hematologic, biochemical and genotoxic biomarkers. The population in analysis consisted of 60 farm workers from the municipalities of Barras and José de Freitas occupationally exposed to pesticides and 55 control individuals with no history of exposure to agrochemicals. To obtain the characteristics of the population, a social-epidemiological questionnaire was applied, recommended by International Commission for Protection Against Environmental Mutagens and Carcinogens-ICPEMC. 10 mL of peripheral blood were collected for haematological, biochemical and comet assay analyses, all of which were processed by LACEN-PI. The mean age was 34 years, of black ethnicity, mostly with an average of 13.55 years of work, workload of 41.5 weekly hours and 50% of workers used at least one type of PPE. In what concerns lifestyle, 66.7% of the exposed workers said they did not consume vegetables, 41.7% were smokers and 73.3% consumed alcohol. Of the total of the exposed group, 33.3% used prescribed medication and 66.7% used non-prescribed medication. In the study, it was evidenced a higher use of herbicides (81.1%) and insecticides (16.3%) in agriculture. In the group of exposed workers, 55% had leucopenia and 6.7% showed a decrease in the red blood cell count. It was found variation in plasmatic creatinine (p < 0.05); in liver enzymes and alkaline phosphatise (p < 0.01) when comparing the exposed and the non-exposed groups. In the results of the comet assay, the exposed group showed, in comparison with the non-exposed group, a mean of (32.13 vs. 10.12) of damage index and damage frequency of (21.82 vs. 9.38), respectively. In class 1, the genotoxicity observed was 17% for the exposed and 9% for the non-exposed. There was no significance between DNA damage and the following variables: workload, non-use of PPE, smoking, consumption of alcohol and non-consumption of vegetables. We concluded that workers exposed to pesticides presented toxic variations and genetic instability, which was evidenced by enzymatic variation and damages to the DNA, which thus demonstrates the importance of biomonitoring of workers as a strategy of occupational health surveillance in the state of Piauí.